Towards a one health approach to WASH to tackle zoonotic disease and promote health and wellbeing - Dickin, S.; Dagerskog, L.; Dione, Michel M.; Thomas, Lian F.; Arcilla, J. (2025)
There is increasing awareness that exposure to animal faeces contributes to the global burden of diarrheal disease, as well as other zoonotic diseases. This recognition has prompted a re-evaluation of water, sanitation, and hygiene (WASH) interventions to address animal-related transmission pathways. However, current efforts focus primarily on animal faeces within household environments, neglecting other critical human-animal interactions that favour contamination such as animal handling. We advance growing efforts to link One Health and WASH from a risk perspective, reviewing implications for humans, animals, as well as the environment, which has been overlooked. We then discuss how a comprehensive OH-WASH approach can move beyond risks to also enable opportunities to promote health, equity, climate resilience, and other benefits. This framing offers possibilities to reduce disease transmission and enhance biosecurity, while addressing interconnected challenges facing low- and middle-income countries including food insecurity and agricultural livelihoods, animal health and welfare, and ecosystem degradation from excessive nutrients found in excreta.